Semantic activation in LSD: evidence from picture naming. Issue 10 (25th November 2016) - Family, Neiloufar; Vinson, David; Vigliocco, Gabriella; Kaelen, Mendel; Bolstridge, Mark; Nutt, David J.; Carhart-Harris, Robin L.
ABSTRACT: Lysergic acid diethylamide (LSD) is a classic psychedelic drug that alters cognition in a characteristic way. It has been suggested that psychedelics expand the breadth of cognition via actions on the central nervous system. Previous work has shown changes in semantic processing under psilocybin (a related psychedelic to LSD) that are consistent with an increased spread of semantic activation. The present study investigates this further using a picture-naming task and the psychedelic, LSD. Ten participants completed the task under placebo and LSD. Results revealed significant effects of LSD on accuracy and error correction that were consistent with an increased spread of semantic activation under LSD. These results are consistent with a generalised "entropic" effect on the mind. We suggest incorporating direct neuroimaging measures in future studies, and to employ more naturalistic measures of semantic processing that may enhance ecological validity.